Information Media Innovation as a Support for the Development of BTPN Syariah MSMEs in the Kromengan Region, Malang Regency - Ardiwinata, Muhammad Everest; M. Taufiq; Oktafia, Renny (PT Inovasi Pratama Internasional, 2025)
This community service aims to develop and implement innovations in the use of information media as a support for the development of Micro, Small and Medium Enterprises (MSMEs) that are customers of the Sharia National Retirement Savings Bank (BTPN) in the Kromengan area, Malang Regency. This service proposes innovative strategies such as optimizing the increase in the use of information technology to support the marketing and promotion of MSME products. Service steps include identifying the needs of MSMEs, analyzing existing information media, developing innovative strategies based on the identified needs, and implementing training and mentoring for MSME owners in implementing this strategy. Monitoring and evaluation are carried out periodically to measure the impact of information media strategies on increasing sales and visibility of MSMEs in the Kromengan area. The method used is the ABCD (Asset Based Community Development) method, which is an approach model that emphasizes one point of purpose, namely in the inventory of assets that support community empowerment activities The results of this service show that the use of innovative strategies in information media can significantly increase market access and sales of MSMEs in the Kromengan area.